Impact of plant ecotype on Bacillus-mediated growth promotion : extending beyond the standard model plant - Matzén, Staffan (SLU/Dept. Of Plant Biology, 2018)
This study investigated how bacterial treatment modulates plant growth. Bacillus amyloliquefaciens UCMB5113 was used for treatment of several different natural accessions (ecotypes) as well as mutants of Arabidopsis thaliana. Treatment effect on plant root architecture was studied in particular.